ANALISIS KUALITAS AIR SUMUR DI DKI JAKARTA BERDASARKAN ZAT PADAT TERLARUT MENGGUNAKAN REGRESI LINEAR SEDERHANA - A Haikal, Vikri (Jurnal Riset Informatika dan Teknologi Informasi, 2024)
Water is one of the most important basic human needs. Good water quality is essential for maintaining human health. One way to determine water quality is to test water quality parameters. This study aims to analyze the quality of groundwater in DKI Jakarta based on dissolved solids. The research data were obtained from Open Data Jakarta. The data used included groundwater quality parameters, namely dissolved solids (TDS). The results showed that TDS has a significant relationship with the quality of groundwater in DKI Jakarta. The formed linear regression model can be used to predict the quality of groundwater in DKI Jakarta.